A Study of a New Intelligent Key System for Substation - Dan Chen; Yefei Yue; Hongfen Jiang; Xiaorong Zhao; Liyuan Wang (Institute of Advanced Engineering and Science, 2014)
Aiming at the demand of production management of power system, a new intelligent key system applied to substation is created and established. Based on the operating mode of the system, the paper puts forward the design of intelligent key based on RFID technology. It expounds the hardware of the system, which adopts advanced ARM technology to develop an intelligent key system, combined with RF signal recognition technology, OLED display, data storage, keyboard input and other functions, in order to meet the functional requirements for intelligence. Its software uses the embedded μC/OS-Ⅱto achieve the signal reception of the new intelligent key system. After tested, the key works well. The system is characterized by more portability, large storage capacity, more functions, friendly interface and other noticeable features.